Kajian Etnomatematika pada Alat Musik Kolintang Terhadap Pembelajaran Matematika - Diola, Marcelina Meiliana; Auxillia, Maria Novena; Ningrum, Lusia Adven (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Kolintang is a traditional marimbaphone family instrument from North Sulawesi Province which has been modified in various forms of appearance with chromatic melodies. Kolintang is a traditional musical instrument which is still used by some people in Indonesia. Kolintang is a type of traditional musical instrument that groups can relate to learning mathematics. This study aims to explore the form of the Kolintang musical instrument and relate it to learning mathematics. This type of research is qualitative with an ethnographic approach. The data obtained through the process of observation and documentation. Observations and documentation were carried out at Maria Assumpta Middle School Klaten on 5 types of kolintang namely, contra bass, baritone, bass, alto, and tenor. The result obtained is the general formula for the arithmetic sequence obtained from the length of the kolintang blade.